Teacher Perspectives on Supporting Students With Stuttering in Schools and Preschools - Anna Michalczyk; Aleksanda Ślusarczyk (Horyzonty Wychowania)
RESEARCH OBJECTIVE: The purpose of the research presented in this article was to explore the opinions of kindergarten and elementary school teachers on supporting students with stuttering in their functioning within educational institutions.